Analisis Pertumbuhan Perbankan Syariah - Aulia Rahman; Ratna Sari Dewi (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2019)
This study aims to provide information about the development of Islamic financialinstitutions, especially in Islamic banking in Indonesia, which is certainly seenfrom the development of the number of offices and profits obtained by Islamicbanking. The method used in the research is descriptive qualitative method, wherethe researcher will collect data related to the development of Islamic banking, thedata is taken from the official website of the Indonesian Bani, and the FinancialServices Authority or often referred to as OJK. The results obtained in this study,that Islamic banks continue to experience an increase in the number of officesfrom year to year, although there are several years experiencing decline, as well asprofits earned by Islamic banks. But despite the decline, Islamic banks continuedto show their existence and continue to develop Islamic banking itself.